A novel environment-friendly inorganic dry powder coating and a preparation method thereof

CN122878784APending Publication Date: 2026-10-09HENAN YUBO INTELLIGENT ENVIRONMENTALLY FRIENDLY BUILDING MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511431985.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-09
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

这种折中带来两方面问题:其一,矿物基层的碱-盐-水耦合环境没有得到根本适配,涂层在高湿或冷凝条件下仍可能发生发白、鼓泡与剥落;其二,加入有机组分后,透湿与耐污往往呈此消彼长的关系,过度致密化虽能提升耐擦,却削弱水汽扩散通道,易诱发鼓包与内应力集中,同时环保属性与耐火等级也随之打折扣

Benefits of technology

与现有技术相比,本发明通过在完全无机体系内构建具有先后顺序与空间分布差异的多层次骨架,有效协同提升了涂层的粘结强度、致密性、透湿性与防霉性能。通过喷雾干燥水玻璃粉在矿物基层表面引发硅化反应,形成以化学键合为主的界面网络,兼顾初期粘结强度与长期稳定性;沉淀法二氧化硅与微硅粉在体相中构建连续的纳米桥联结构,赋予表层适宜的致密度与耐磨性,同时保留连通孔道,避免因结构过密导致水汽滞留和鼓包风险。与传统无机配方中简单共混功能粉体的方式不同,本发明在重质碳酸钙等骨料表面原位生长层状双氢氧化物片层,形成定域壳层界面。该界面能有效抑制离子迁移、缓冲湿度波动并引导裂纹偏转,从而降低返碱和盐花现象的发生概率,延缓微裂纹扩展对涂层外观与耐久性的影响。在碱金属组成与水玻璃模数方面,通过对体系碱度与缩聚速率的协同控制,兼顾了界面反应活性与凝胶收缩抑制,使初期耐水白化与长期粘结保持处于受控状态。防霉机理则采用纳米氧化锌与银离子负载无机载体的复合路径,依托上述定域壳层与纳米桥联结构形成近表的缓释与定点抑菌作用,即使涂层在服役过程中因碳化导致碱度下降,仍能保持较为稳定的防霉性能,避免了对高碱环境的短期依赖。通过云母、煅烧高岭土与空心玻璃微珠的级配优化,涂层的孔径分布与导热路径得到协同调控,有效分散由冷凝和干湿循环引起的尺寸与应力波动。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122878784A_ABST
    Figure CN122878784A_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of dry powder paint, and particularly relates to a novel environment-friendly inorganic dry powder paint and a preparation method thereof. The novel environment-friendly inorganic dry powder paint is composed of 92-96% of a structural cementitious framework component and 4-8% of a functional stable component according to the mass percentage; the structural cementitious framework component is composed of the following raw materials: spray-dried potassium water glass powder, Li2CO3 powder, precipitated silica powder, micro-silica powder, LDH shell CaCO3, talc powder, calcined kaolin, mica powder, quartz powder, rutile and hollow glass microbeads; the functional stable component is composed of the following raw materials: nano-ZnO, Ag + loaded zeolite, sodium hexametaphosphate, bentonite, diatomite and tricalcium phosphate. The present application constructs a multi-level framework in a completely inorganic system, promotes silicification by spray-dried water glass powder, builds a nano bridge by precipitated silica and micro-silica powder, generates an LDH shell in situ by heavy calcium, and cooperates with a multi-stage process to simultaneously improve the bonding, mildew resistance and alkali resistance of the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of dry powder coating technology, specifically relating to a novel environmentally friendly inorganic dry powder coating and its preparation method. Background Technology

[0002] Currently, the interior wall coating market is dominated by liquid coatings with various organic resins as the main film-forming agents, such as acrylic, vinyl, and their copolymer systems. These materials rely on emulsifiers, film-forming aids, and various organic additives to achieve rheological changes and film-forming continuity during application. Before and after application, volatile organic compounds, residual monomers, and plasticizers are released, which are difficult to completely dissipate in a short time in residential settings, easily causing long-term fluctuations in indoor air quality and lingering odors. Because organic coatings require a relatively stable temperature and humidity environment and a high degree of substrate flatness, renovation or occupancy applications place stricter demands on substrate leveling, moisture content, and alkalinity control. If the substrate has high moisture content or condensation, common failure phenomena include water whitening, blistering, peeling, and interlayer delamination. Furthermore, mineral substrates are generally strongly alkaline and accompanied by the migration of soluble salts. Organic resins and these inorganic substrates mainly adhere physically; affected by efflorescence and moisture cycles, the coating is prone to adhesion degradation and discoloration, resulting in higher maintenance costs.

[0003] To mitigate health and safety risks, so-called inorganic coatings based on inorganic binders have emerged on the market. However, a significant portion of these still incorporate liquid organic resins to compensate for flexibility and scrub resistance, effectively creating an "inorganic-organic composite" approach. This compromise presents two problems: First, the alkali-salt-water coupling environment of the mineral substrate is not fundamentally adapted, and the coating may still whiten, blister, and peel under high humidity or condensation conditions. Second, with the addition of organic components, moisture permeability and stain resistance often have an inverse relationship; excessive densification, while improving scrub resistance, weakens moisture diffusion channels, easily inducing blistering and internal stress concentration, while also compromising environmental properties and fire resistance. More practically, the storage, transportation, and on-site management of liquid products are sensitive to temperature, humidity, and open time, easily leading to batch-to-batch color differences and inconsistent feel during renovations and small-batch construction, making it difficult to meet the comprehensive demands of cultural heritage preservation, medical care, and education for low odor, low emissions, and fire safety. Summary of the Invention

[0004] In view of the shortcomings of the existing technology, the purpose of this invention is to provide a novel environmentally friendly inorganic dry powder coating and its preparation method.

[0005] The technical effects described in this invention are achieved through the following technical solution: a novel environmentally friendly inorganic dry powder coating, which is composed of 92-96% structural cementitious skeleton components and 4-8% functional stabilizing components by mass percentage; Preferably, the structural cementitious skeleton component comprises the following raw materials in parts by weight: 12-18 parts spray-dried potassium silicate powder, 0.05-0.15 parts Li2CO3 powder, 4-7 parts precipitated silica powder, 2-4 parts microsilica powder, 25-35 parts LDH shell CaCO3, 8-12 parts talc powder, 4-8 parts calcined kaolin, 3-6 parts mica powder, 4-8 parts quartz powder, 6-10 parts rutile, and 1.5-3 parts hollow glass microspheres; Preferably, the modulus of the spray-dried potassium silicate powder is 3.5 to 3.9; it is a powder produced by spray drying liquid potassium silicate with a modulus of 3.5 to 3.9 and a mass concentration of 30 to 40%; the spray drying process conditions are: inlet air temperature 190 to 210°C, outlet air temperature 85 to 95°C, atomization pressure 0.25 to 0.35 MPa, and feed rate 5 to 10 L / h. Preferably, the specific surface area of ​​the precipitated silica powder is 180–220 m² / g. 2 / g; Preferably, the mica powder has a particle size of 300-600 mesh; Preferably, the hollow glass microspheres have a particle size of 60–125 μm; Preferably, the specific preparation steps of the LDH shell CaCO3 are as follows: S1: Disperse heavy CaCO3 in deionized water, stir until evenly dispersed, adjust the pH to 10-10.4 with ammonia water to obtain a 30-40 wt% slurry; add Mg(NO3)2·6H2O to deionized water, stir until evenly dissolved to obtain a 1-1.5 mol / L solution A; add Al(NO3)3·9H2O to deionized water, stir until evenly dissolved to obtain a 0.5-0.8 mol / L solution B; S2: Simultaneously add solutions A and B from step S1 to the slurry dropwise over 45–90 minutes, maintaining a constant pH of 10–10.4 with ammonia water during the addition. After addition is complete, continue stirring for 30–60 minutes, allow to stand and age for 30–60 minutes, bubble with CO2 for 10–20 minutes, centrifuge, and wash repeatedly with deionized water until the filtrate conductivity is <150 μS / cm and NO3- is <10%. - <50ppm; vacuum dried at 105℃ for 4-6 hours, and screened through a 200-mesh sieve to obtain LDH shell CaCO3; Preferably, in step S2, the volume ratio of solution A, solution B, and slurry is 0.018–0.025:0.07–0.08:1; Preferably, the functional stabilizing component comprises the following raw materials in parts by weight: 0.3–0.7 parts nano-ZnO, 0.01–0.05 parts Ag. +Supported zeolite, 0.05–0.2 parts sodium hexametaphosphate, 0.3–0.6 parts bentonite, 0.5–1 parts diatomite, and 0.15–0.3 parts tricalcium phosphate; Preferably, the Ag + The supported zeolite was prepared by a conventional ion exchange method; Preferably, another aspect of the present invention provides a method for preparing a novel environmentally friendly inorganic dry powder coating, the specific preparation steps of which are as follows: S101: Add LDH shell CaCO3, talc powder, calcined kaolin, mica powder, quartz powder and hollow glass microspheres into the mixer in sequence, with the screw conveyor at 20-35 rpm and the plow blade at 60-120 rpm, and mix for 6-8 minutes. S102: Continue to add spray-dried potassium silicate powder, Li2CO3 powder, precipitated silica powder, microsilica powder, rutile, ZnO, and Ag to the mixer in step S101 in sequence. + The mixture is loaded with zeolite, sodium hexametaphosphate, bentonite, diatomite and tricalcium phosphate, and mixed with a spiral at 30-45 rpm and a plow at 90-160 rpm for 8-10 min. After screening through a 150-mesh screen, it is homogenized twice at low speed in the same machine to obtain an inorganic dry powder coating. Preferably, in step S102, the parameters for the low-speed secondary homogenization are: spiral ribbon 20-25 rpm, plow blade 60-80 rpm, and mixing for 5-6 min.

[0006] The beneficial effects of this invention are as follows: Compared with existing technologies, this invention effectively and synergistically improves the coating's adhesion strength, density, moisture permeability, and mildew resistance by constructing a multi-layered framework with sequential and spatially differentiated structures within a completely inorganic system. Spray-dried water glass powder initiates a silicification reaction on the mineral substrate surface, forming an interface network primarily based on chemical bonding, balancing initial adhesion strength and long-term stability. Precipitated silica and microsilica powder construct a continuous nano-bridged structure in the bulk phase, imparting suitable density and wear resistance to the surface layer while retaining interconnected channels to avoid moisture retention and blistering risks due to excessive density. Unlike the simple blending of functional powders in traditional inorganic formulations, this invention grows layered double hydroxide sheets in situ on the surface of aggregates such as heavy calcium carbonate, forming a localized shell interface. This interface effectively inhibits ion migration, buffers humidity fluctuations, and guides crack deflection, thereby reducing the probability of alkali return and salt bloom phenomena, and delaying the impact of microcrack propagation on the coating's appearance and durability. Regarding the alkali metal composition and water glass modulus, the system's alkalinity and condensation rate are synergistically controlled, balancing interfacial reactivity and gel shrinkage inhibition, thus maintaining controlled initial water resistance and long-term adhesion. The anti-mold mechanism employs a composite pathway of nano-zinc oxide and silver ion-loaded inorganic carriers. Relying on the aforementioned localized shell and nano-bridging structure, it forms near-surface slow-release and targeted antibacterial effects. Even if the coating's alkalinity decreases due to carbonization during service, it maintains relatively stable anti-mold performance, avoiding short-term dependence on high-alkaline environments. Through optimized gradation of mica, calcined kaolin, and hollow glass microspheres, the coating's pore size distribution and thermal conductivity pathway are synergistically regulated, effectively dispersing dimensional and stress fluctuations caused by condensation and wet-dry cycles.

[0007] This invention employs a two-stage mixing process—first the framework, then the function—along with secondary low-speed homogenization, coupled with appropriate sieving and powder moisture control. This significantly reduces local enrichment of fine components and batch-to-batch fluctuations, minimizing construction defects and uneven appearance. This timing and process window not only ensure material uniformity but also directly determines the formation efficiency and integrity of the interface network, nano-bridging, and localized shell. The entire process of this invention does not introduce organosilicon, polymers, or organic surfactants. The silver source exists as an inorganic carrier, making migration and yellowing risks controllable. The system has natural advantages in fire safety, low odor, and environmental compliance, making it suitable for indoor environments with comprehensive requirements for health, durability, and maintenance costs. In summary, this invention, through the synergistic effects of modulus and alkali metal composition regulation, inorganic nano-bridging, in-situ shell localization, and graded pore size spectrum design, simultaneously improves key properties such as antibacterial, environmental protection, anti-alkali reversion, and long-lasting anti-mildew effects without relying on organic components. Attached Figure Description

[0008] Figure 1 The diagram shows the adhesion test results of the dry powder coatings prepared in Example 1 and Comparative Examples 1-4 of the present invention. Figure 2 The pH change results of the durability test of the dry powder coatings prepared in Example 1 and Comparative Examples 1-4 of the present invention are shown in the figure. Figure 3 The graph shows the results of the adhesion strength variation in the durability test of the dry powder coatings prepared in Example 1 and Comparative Examples 1-4 of this invention. Detailed Implementation

[0009] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Unless otherwise specified, the raw materials involved in the present invention are all purchased through conventional commercial channels. Experimental methods without specific conditions are conventional methods and conditions well known in the art, or according to the conditions recommended by the instrument manufacturer.

[0010] Example 1: A novel environmentally friendly inorganic dry powder coating, which is composed of 95% structural cementitious skeleton component and 5% functional stabilizing component by mass percentage; The structural cementitious skeleton component comprises the following raw materials in parts by weight: 15 parts spray-dried potassium silicate powder, 0.1 parts Li2CO3 powder, 6 parts precipitated silica powder, 3 parts microsilica powder, 32 parts LDH shell CaCO3, 10 parts talc powder, 6 parts calcined kaolin, 5 parts mica powder, 6 parts quartz powder, 8 parts rutile and 2.5 parts hollow glass microspheres; The spray-dried potassium silicate powder has a modulus of 3.7; it is a powder made from liquid potassium silicate with a modulus of 3.7 and a mass concentration of 35% by spray drying; the spray drying process conditions are: inlet air temperature 200℃, outlet air temperature 90℃, atomization pressure 0.3MPa, and feed rate 8L / h. The specific preparation steps for the LDH shell CaCO3 are as follows: S1: Disperse heavy CaCO3 in deionized water, stir until evenly dispersed, adjust pH to 10.2 with ammonia water to obtain a 35wt% slurry; add Mg(NO3)2·6H2O to deionized water, stir until evenly dissolved to obtain a 1.3mol / L solution A; add Al(NO3)3·9H2O to deionized water, stir until evenly dissolved to obtain a 0.7mol / L solution B; S2: Simultaneously add 22 mL of solution A and 75 mL of solution B from step S1 to 1000 mL of slurry, adding dropwise over 60 min. During the addition, maintain a constant pH of 10.2 with ammonia water. After the addition is complete, continue stirring for 45 min, allow to stand and age for 45 min, bubble with CO2 for 15 min, centrifuge, and wash repeatedly with deionized water until the filtrate conductivity is <150 μS / cm and NO3- content is <10%. -<50ppm; vacuum dried at 105℃ for 5h, and screened through a 200-mesh sieve to obtain LDH shell CaCO3; The functional stabilizing component comprises the following raw materials in parts by weight: 0.5 parts nano-ZnO, 0.03 parts Ag + The mixture contains 0.12 parts of sodium hexametaphosphate, 0.5 parts of bentonite, 0.8 parts of diatomaceous earth, and 0.25 parts of tricalcium phosphate. The specific preparation steps of the novel environmentally friendly inorganic dry powder coating are as follows: S101: Add LDH shell CaCO3, talc powder, calcined kaolin, mica powder, quartz powder and hollow glass microspheres into the mixer in sequence, with the screw conveyor at 30 rpm and the plow blade at 100 rpm, and mix for 7 min. S102: Continue to add spray-dried potassium silicate powder, Li2CO3 powder, precipitated silica powder, microsilica powder, rutile, ZnO, and Ag to the mixer in step S101 in sequence. + Zeolite, sodium hexametaphosphate, bentonite, diatomaceous earth, and tricalcium phosphate were loaded and mixed for 9 minutes at 40 rpm with a spiral ribbon and 150 rpm with a plow blade. After sieving through a 150-mesh screen, the mixture was homogenized again at low speed in the same machine at 24 rpm with a spiral ribbon and 70 rpm with a plow blade for 5.5 minutes to obtain an inorganic dry powder coating.

[0011] Example 2: A novel environmentally friendly inorganic dry powder coating, which is composed of 96% structural cementitious skeleton component and 4% functional stabilizing component by mass percentage; The structural cementitious skeleton component comprises the following raw materials in parts by weight: 18 parts spray-dried potassium silicate powder, 0.15 parts Li2CO3 powder, 7 parts precipitated silica powder, 4 parts microsilica powder, 35 parts LDH shell CaCO3, 12 parts talc powder, 8 parts calcined kaolin, 6 parts mica powder, 8 parts quartz powder, 10 parts rutile and 3 parts hollow glass microspheres; The spray-dried potassium silicate powder has a modulus of 3.9; it is a powder produced by spray drying liquid potassium silicate with a modulus of 3.9 and a mass concentration of 40%; the spray drying process conditions are: inlet air temperature 210℃, outlet air temperature 95℃, atomization pressure 0.35MPa, and feed rate 10L / h. The specific preparation steps for the LDH shell CaCO3 are as follows: S1: Disperse heavy CaCO3 in deionized water, stir until evenly dispersed, adjust pH to 10.4 with ammonia water to obtain a 40wt% slurry; add Mg(NO3)2·6H2O to deionized water, stir until evenly dissolved to obtain a 1.5mol / L solution A; add Al(NO3)3·9H2O to deionized water, stir until evenly dissolved to obtain a 0.8mol / L solution B; S2: Simultaneously add 25 mL of solution A and 80 mL of solution B from step S1 to 1000 mL of slurry, adding dropwise for 90 min. During the addition, maintain a constant pH of 10.4 with ammonia water. After the addition is complete, continue stirring for 60 min, allow to stand and age for 60 min, bubble with CO2 for 20 min, centrifuge, and wash repeatedly with deionized water until the filtrate conductivity is <150 μS / cm and NO3- content is <10%. - <50ppm; vacuum dried at 105℃ for 6h, and screened through a 200-mesh sieve to obtain LDH shell CaCO3; The functional stabilizing component comprises the following raw materials in parts by weight: 0.7 parts nano-ZnO, 0.05 parts Ag + Loaded zeolite, 0.2 parts sodium hexametaphosphate, 0.6 parts bentonite, 1 part diatomaceous earth and 0.3 parts tricalcium phosphate; The specific preparation steps of the novel environmentally friendly inorganic dry powder coating are as follows: S101: Add LDH shell CaCO3, talc powder, calcined kaolin, mica powder, quartz powder and hollow glass microspheres into the mixer in sequence, and mix for 8 minutes with the ribbon at 35 rpm and the plow blade at 120 rpm. S102: Continue to add spray-dried potassium silicate powder, Li2CO3 powder, precipitated silica powder, microsilica powder, rutile, ZnO, and Ag to the mixer in step S101 in sequence. + Zeolite, sodium hexametaphosphate, bentonite, diatomaceous earth, and tricalcium phosphate were loaded and mixed for 10 minutes at 45 rpm with a spiral feed and 160 rpm with a plow. After sieving through a 150-mesh screen, the mixture was homogenized again at low speed in the same machine at 25 rpm with a spiral feed and 80 rpm with a plow. The resulting inorganic dry powder coating was obtained.

[0012] Example 3: A novel environmentally friendly inorganic dry powder coating, which is composed of 92% structural cementitious skeleton component and 8% functional stabilizing component by mass percentage; The structural cementitious skeleton component comprises the following raw materials in parts by weight: 12 parts spray-dried potassium silicate powder, 0.05 parts Li2CO3 powder, 4 parts precipitated silica powder, 2 parts microsilica powder, 25 parts LDH shell CaCO3, 8 parts talc powder, 4 parts calcined kaolin, 3 parts mica powder, 4 parts quartz powder, 6 parts rutile and 1.5 parts hollow glass microspheres; The spray-dried potassium silicate powder has a modulus of 3.5; it is a powder produced by spray drying liquid potassium silicate with a modulus of 3.5 and a mass concentration of 30%; the spray drying process conditions are: inlet air temperature 190℃, outlet air temperature 85℃, atomization pressure 0.25MPa, and feed rate 5L / h. The specific preparation steps for the LDH shell CaCO3 are as follows: S1: Disperse heavy CaCO3 in deionized water, stir until evenly dispersed, adjust pH to 10 with ammonia water to obtain a 30wt% slurry; add Mg(NO3)2·6H2O to deionized water, stir until evenly dissolved to obtain a 1mol / L solution A; add Al(NO3)3·9H2O to deionized water, stir until evenly dissolved to obtain a 0.5mol / L solution B; S2: Simultaneously add 18 mL of solution A and 70 mL of solution B from step S1 to 1000 mL of slurry, adding dropwise over 45 min. During the addition, maintain a constant pH of 10 using ammonia water. After the addition is complete, continue stirring for 30 min, allow to stand and age for 30 min, bubble with CO2 for 10 min, centrifuge, and wash repeatedly with deionized water until the filtrate conductivity is <150 μS / cm and NO3- content is <10%. - <50ppm; vacuum dried at 105℃ for 4h, and screened through a 200-mesh sieve to obtain LDH shell CaCO3; The functional stabilizing component comprises the following raw materials in parts by weight: 0.3 parts nano-ZnO, 0.01 parts Ag + The mixture contains 0.05 parts of zeolite, 0.3 parts of sodium hexametaphosphate, 0.5 parts of bentonite, 0.15 parts of diatomite, and 0.15 parts of tricalcium phosphate. The specific preparation steps of the novel environmentally friendly inorganic dry powder coating are as follows: S101: Add LDH shell CaCO3, talc powder, calcined kaolin, mica powder, quartz powder and hollow glass microspheres into the mixer in sequence, with the screw conveyor at 20 rpm and the plow blade at 60 rpm, and mix for 6 min. S102: Continue to add spray-dried potassium silicate powder, Li2CO3 powder, precipitated silica powder, microsilica powder, rutile, ZnO, and Ag to the mixer in step S101 in sequence. + Zeolite, sodium hexametaphosphate, bentonite, diatomaceous earth, and tricalcium phosphate were loaded and mixed for 8 minutes at 30 rpm with a spiral ribbon and 90 rpm with a plow blade. After sieving through a 150-mesh screen, the mixture was homogenized a second time at low speed in the same machine at 20 rpm with a spiral ribbon and 60 rpm with a plow blade for 5 minutes to obtain an inorganic dry powder coating.

[0013] Comparative Example 1: The raw materials and processes of Comparative Example 1 are basically the same as those of Example 1. The main difference is that the in-situ LDH shell layer is removed in Comparative Example 1 and only unmodified heavy calcium carbonate is used to replace it to maintain the consistency of the ratio and solid content; the remaining steps and parameters are the same as those of Example 1.

[0014] Comparative Example 2: The raw materials and processes of Comparative Example 2 are basically the same as those of Example 1. The main difference is that in Comparative Example 2, precipitated silica is replaced with inert mineral filler quartz powder of similar particle size to maintain the total mass and gradation. The remaining steps and parameters are the same as those of Example 1.

[0015] Comparative Example 3: The raw materials and processes of Comparative Example 3 are basically the same as those of Example 1. The main difference is that lithium source Li2CO3 powder is not added in Comparative Example 3, the amount and modulus of spray-dried potassium water glass powder are kept unchanged, and the total inorganic solids in the formula are made up by an equal mass of matrix filler talc powder; the remaining steps and parameters are consistent with those of Example 1.

[0016] Comparative Example 4: The formulation of Comparative Example 4 is consistent with that of Example 1. The main difference is that in Comparative Example 4, the two-stage mixing of skeleton and function in steps S101-102 and the secondary low-speed homogenization after sieving are changed to one-step mixing and no secondary homogenization is performed; the remaining steps and parameters are consistent with those of Example 1.

[0017] Performance testing: The inorganic dry powder coating prepared by this invention was stirred and allowed to stand for aging at a water-to-powder ratio of 30:100, and then subjected to the following partial performance tests. Environmental testing: Based on the standards of GB 18582-2020 and GB / T 23984-2009, the VOC content, formaldehyde content and total benzene series compounds of the inorganic dry powder coatings prepared in Examples 1-3 and Comparative Examples 1-4 of this invention were tested. The test results are shown in Table 1 below.

[0018] Table 1. Environmental protection test results of inorganic dry powder coatings in the examples and comparative examples

[0019] Based on the results in Table 1, the present invention uses a technical strategy of being entirely inorganic, zero resin and zero organic additives. The above three environmental protection indicators are essentially dominated by the formula attributes and have little to do with structural and process variables such as whether an LDH shell is set, whether SiO2 is added, whether a trace lithium source is used, and the mixing sequence. The examples and comparative examples all show the same zero-emission safety level.

[0020] Antibacterial properties test: Based on the standard HG / T 3950-2007, the antibacterial properties of the inorganic dry powder coatings prepared in Examples 1-3 and Comparative Examples 1-4 of this invention were tested, and the results are shown in Table 2 below.

[0021] Table 2. Antibacterial test results of inorganic dry powder coatings in the examples and comparative examples

[0022] Based on the results in Table 2, the inorganic coating prepared in this invention achieved an inhibition rate of 99.9% against Aspergillus niger, Escherichia coli, and Staphylococcus aureus, demonstrating excellent antibacterial properties. Comparative Example 1, lacking an LDH interface structure, experienced decreased uniformity in the dispersion of ZnO and silver-loaded particles within the system, leading to faster dilution and migration, and increased fluctuations in the local microenvironment. Consequently, both short-term and long-term inhibition of bacteria and Aspergillus niger were significantly reduced. In Comparative Example 2, replacing key components with inert quartz resulted in a lack of effective nanoscale bridging and densification structure regulation in the near-surface region. This facilitated the formation of a continuous wet film by liquid water, providing favorable conditions for biofilm initiation and spore germination. Consequently, the antifungal inhibition performance significantly decreased, further affecting bacterial inhibition. In Comparative Example 3, without a lithium source, early gel shrinkage and ion migration were difficult to effectively suppress, leading to increased microcracks and local component enrichment, weakening the effectiveness and durability of the antibacterial components, resulting in a decline in the overall inhibition rate against bacteria and mold. In contrast, Comparative Example 4 uses a one-step mixing process, which easily causes functional powder agglomeration and uneven regional distribution, resulting in significant spatial dispersion of antibacterial activity and the appearance of local failure areas. This leads to a decrease in the overall statistical antibacterial rate and long-term stability, especially in terms of mold inhibition.

[0023] Fire resistance test: Based on the test methods of GB / T 5464-2010 and GB / T 14402-2007, the fire resistance performance of the inorganic dry powder coatings prepared in Examples 1-3 and Comparative Examples 1-4 of this invention was tested, and the results are shown in Table 3 below.

[0024] Table 3. Fire resistance test results of inorganic dry powder coatings in the examples and comparative examples

[0025] Based on the results in Table 3, the coating system of this embodiment is entirely inorganic, fundamentally eliminating the presence of combustibles and causing its total calorific value to approach the detection limit. During the thermal response, the LDH shell, through endothermic dehydroxylation and hydrate release, constructs an effective endothermic barrier in the early stage of heating. In addition, the precipitated SiO2 forms a dense and interconnected porous structure through the nano-bridging effect, effectively blocking the channels of heat conduction and convection, jointly achieving the lowest temperature rise and zero sustained combustion time. Moreover, its slight mass loss can be entirely attributed to the loss of adsorbed water and crystal water. In Comparative Example 1, after the in-situ LDH shell was removed, the lack of LDH endothermic decomposition and endothermic effect reduced the initial thermal buffering capacity, and the surface temperature rapidly crossed the critical point. The lack of a lamellar transition zone between particles and matrix made it easy for microcracks to propagate to the surface under thermal shock, causing particle detachment and the formation of thermal bridges, which accelerated heat flow penetration and also caused dust to produce brief glow or residual flame in the flame zone. In Comparative Example 2, replacing precipitated silica with inert quartz weakened the nano-bridging effect, shifted the pore size distribution to the right, enhanced capillary convection of vapor within the pores, and increased the local temperature and risk of water whitening due to the heat-humidity coupling effect. Simultaneously, due to the lack of secondary alkali treatment and nano-densification, it was difficult to form a continuous micro-ceramicized dense band on the surface after heating, resulting in a slightly higher temperature rise and mass loss. In Comparative Example 3, removing the lithium source disrupted the condensation-shrinkage equilibrium of the silicate gel. Existing microcracks and stresses at room temperature were exacerbated by heating, forming more through-type thermal pathways, increasing heat flow penetration and equivalent heat release. Although it did not ignite, the thermal response was sharper and the temperature rise was higher. In Comparative Example 4, after changing the two-stage mixing and secondary homogenization to a one-stage mixing, the functional phase and the cemented phase were unevenly distributed, and the near-surface region showed local depletion of nano-SiO2 and metal oxides, making it impossible to construct a continuous endothermic-dense-sintering synergistic region. At the same time, the local accumulation of the framework and hollow microspheres formed a structure with both thermal bridges and air gaps, resulting in a decrease in thermal field uniformity, manifested as a higher temperature rise peak, a longer ignition time, and a greater apparent weight loss.

[0026] Adhesion and durability tests: The inorganic dry powder coatings prepared in Example 1 and Comparative Examples 1-4 were made into flat plates A (150mm×150mm×10mm) and B (300mm×300mm×10mm). A tensile bond strength tester was used to test plate A. A tensile clamp was vertically attached to the coating surface, and the coating was stretched uniformly at a rate of 5mm / min until the coating or interface failed. The maximum tensile force (F) was recorded, and the bond strength (MPa) was calculated. The results are as follows: Figure 1 As shown; Plate B was placed in 60°C and 95%RH for 28 days. One plate was taken on days 0, 7, 14, and 28 for non-destructive testing. The appearance changes are shown in Table 4 below; pH changes are shown below. Figure 2 As shown; the change in pull-out bond strength under destructive testing is as follows: Figure 3 As shown.

[0027] Table 4. Durability test results of the inorganic dry powder coatings in the examples and comparative examples.

[0028] Based on Table 4, Figure 2 and Figure 3 As a result, the dry powder coating prepared in the embodiments of the present invention has high initial bonding strength, and its retention rate remains high after 28 days of heat and humidity. The pH value decreases steadily over time and enters the safe range early. The appearance shows no significant whitening, salt spots, or bulging throughout the entire cycle. Comparative Example 1 has moderate initial bonding strength, but its retention rate is significantly lower than that of the embodiments. Its pH value remains high for a longer period of time, and its appearance shows whitening at the edges and corners and spot salting from day 7 onwards, accompanied by local micro-bulging in the later stage. Due to the lack of a localized shell structure, there is no buffering mechanism for ion migration and humidity fluctuations, and the interfacial micro-cracks are more likely to penetrate. The failure mode shifts to interfacial peeling, resulting in simultaneous deterioration of strength and appearance. Comparative Example 2 showed slightly lower initial bond strength and weaker durability retention; the pH decreased slowly, and water whitening and wipeable marks appeared on the surface between days 7 and 14, with significant loss of gloss at day 28; the system lacked nano-bridging and secondary alkali absorption, resulting in insufficient surface density and moisture management, and short-term increased liquid water penetration, leading to decreased resistance to water whitening and wipeability. The bond strength degradation mainly stemmed from near-surface weakening. Comparative Example 3 had lower initial strength and the most significant decrease in retention; the pH remained at a high level for a long period, and water whitening and microcrack shadows appeared on the surface early on, with a tendency for localized peeling later; the lack of control over the alkali metal composition led to an imbalance between gel condensation and shrinkage, increased free alkali migration, and the early superposition of internal stress and ion movement formed through channels and localized debonding, causing simultaneous deterioration of both strength and appearance. Comparative Example 4 showed the lowest initial strength and the greatest dispersion, with the lowest retention rate after 28 days. The pH decreased slowly, and the inhomogeneity within the plate was significant. Slight color difference and roller coating marks were visible from day 0, followed by mottled spots, pinholes, blooming, and localized chalking. After disrupting the time sequence of skeleton before function, water glass powder, nano-SiO2, silver loading, and ZnO were spatially unevenly distributed, making it difficult to form a continuous interface network and near-surface functional bands, resulting in failure of weak areas first and amplified intra-batch differences.

[0029] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A novel environmentally friendly inorganic dry powder coating, characterized in that, It is composed of 92-96% structural cementitious skeleton components and 4-8% functional stabilizing components by mass percentage; The structural cementitious skeleton component comprises the following raw materials in parts by weight: 12-18 parts spray-dried potassium silicate powder, 0.05-0.15 parts Li2CO3 powder, 4-7 parts precipitated silica powder, 2-4 parts microsilica powder, 25-35 parts LDH shell CaCO3, 8-12 parts talc powder, 4-8 parts calcined kaolin, 3-6 parts mica powder, 4-8 parts quartz powder, 6-10 parts rutile, and 1.5-3 parts hollow glass microspheres; The functional stabilizing component comprises the following raw materials in parts by weight: 0.3–0.7 parts nano-ZnO, 0.01–0.05 parts Ag. + The ingredients include zeolite, 0.05–0.2 parts sodium hexametaphosphate, 0.3–0.6 parts bentonite, 0.5–1 parts diatomite, and 0.15–0.3 parts tricalcium phosphate.

2. The novel environmentally friendly inorganic dry powder coating according to claim 1, characterized in that, The spray-dried potassium silicate powder has a modulus of 3.5 to 3.9; it is a powder produced by spray drying liquid potassium silicate with a modulus of 3.5 to 3.9 and a mass concentration of 30 to 40%.

3. The novel environmentally friendly inorganic dry powder coating according to claim 2, characterized in that, The specific surface area of ​​the precipitated silica powder is 180–220 m². 2 / g.

4. The novel environmentally friendly inorganic dry powder coating according to claim 3, characterized in that, The mica powder has a particle size of 300-600 mesh.

5. The novel environmentally friendly inorganic dry powder coating according to claim 4, characterized in that, The hollow glass microspheres have a particle size of 60–125 μm.

6. The novel environmentally friendly inorganic dry powder coating according to claim 5, characterized in that, The specific preparation steps for the LDH shell CaCO3 are as follows: S1: Disperse heavy CaCO3 in deionized water, stir until evenly dispersed, adjust pH with ammonia water to obtain slurry; add Mg(NO3)2·6H2O to deionized water, stir until evenly dissolved to obtain solution A; add Al(NO3)3·9H2O to deionized water, stir until evenly dissolved to obtain solution B; S2: Simultaneously add solutions A and B from step S1 to the slurry, continuously adding them while maintaining a constant pH with ammonia during the addition process. After the addition is complete, continue stirring, allow to stand and age, treat with CO2 bubbling, centrifuge, wash repeatedly with deionized water, vacuum dry, and screen to obtain LDH shell CaCO3. In step S2, the volume ratio of solution A, solution B and slurry is 0.018-0.025:0.07-0.08:

1.

7. A method for preparing a novel environmentally friendly inorganic dry powder coating according to any one of claims 1-6, characterized in that, The specific preparation steps are as follows: S101: Add LDH shell CaCO3, talc powder, calcined kaolin, mica powder, quartz powder and hollow glass microspheres into the mixer in sequence and mix. S102: Continue to add spray-dried potassium silicate powder, Li2CO3 powder, precipitated silica powder, microsilica powder, rutile, ZnO, and Ag to the mixer in step S101 in sequence. + The loaded zeolite, sodium hexametaphosphate, bentonite, diatomaceous earth and tricalcium phosphate were mixed; after screening, they were homogenized twice by low-speed processing in the same machine to obtain inorganic dry powder coating.

8. A method for preparing a novel environmentally friendly inorganic dry powder coating according to claim 7, characterized in that, In step S102, the parameters for the low-speed secondary homogenization are: spiral ribbon 20-25 rpm, plow blade 60-80 rpm, and mixing for 5-6 min.